The Incidence of Cartilago-triticea in Bangladeshi Cadaver - Ara, Anjuma; Rahman, Md Mahbubur; Ara, Subaida Gulshan; Chowdhury, Ashraful Islam; Begum, Taslima; Fazilatunnesa, Dr; Chowdhury, Mamunur Rashid (Community Based Medical Journal, 2013)
The cross sectional descriptive type of study was done to see the presence of the cartilago-triticea in relation to age and sexes of Bangladeshi people. A total of 60 human larynges (male 29 and female 31) were collected purposively from dead bodies during routine postmortem examination at the autopsy laboratory of Department of Forensic Medicine and stillborn babies from Gynaecology and Obstetrics Department of Mymensingh Medical College, Mymensingh from October' 2008 to March' 2009. Gross and fine dissection was carried out to see the presence of cartilago-triticea. Cartilago-triticea was found in 58.33% cases. It was observed that the prevalence of cartilago-triticea was more common among females than in males and that their incidence increased with age. DOI: http://dx.doi.org/10.3329/cbmj.v1i1.13821 Community Based Medical Journal Vol.1(1) 2012 8-10